2015
DOI: 10.1682/jrrd.2014.03.0090
|View full text |Cite
|
Sign up to set email alerts
|

Training with robot-applied resistance in people with motor-incomplete spinal cord injury: Pilot study

Abstract: Abstract-People with motor-incomplete spinal cord injury (m-iSCI) can recover basic walking function but still have difficulty performing the skilled walking required for everyday environments. We hypothesized that a robotic-based gait rehabilitation strategy founded on principles of motor learning would be a feasible and potentially effective approach for improving skilled walking in people with m-iSCI. Fifteen individuals with chronic (>1 yr) m-iSCI were randomly allocated to body weight-supported treadmill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 69 publications
2
47
0
Order By: Relevance
“…One pilot RCT study showed that cable-driven robotic resistance training can be used as an adjunct to BWS treadmill training to improve overground walking function in humans with chronic incomplete SCI compared to assistance training [60]. Another pilot RCT study provided evidence that Lokomat-applied resistance training may improve performance in skilled overground walking tasks in patients with chronic motor incomplete SCI compared to conventional Lokomat-assisted gait training [61]. Greater cognitive engagement during training may have elicited greater involvement of cortical regions associated with gait, which are particularly involved in the adjustments of motor output during swing [62], and cable-driven robotic resistance training is promising gait training for chronic incomplete SCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…One pilot RCT study showed that cable-driven robotic resistance training can be used as an adjunct to BWS treadmill training to improve overground walking function in humans with chronic incomplete SCI compared to assistance training [60]. Another pilot RCT study provided evidence that Lokomat-applied resistance training may improve performance in skilled overground walking tasks in patients with chronic motor incomplete SCI compared to conventional Lokomat-assisted gait training [61]. Greater cognitive engagement during training may have elicited greater involvement of cortical regions associated with gait, which are particularly involved in the adjustments of motor output during swing [62], and cable-driven robotic resistance training is promising gait training for chronic incomplete SCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic assisted training wherein full assistance is provided, such that stepping is produced regardless of whether the participant exerts volitional effort, is less effective than methods requiring volitional effort. 51,121 Further, the changes in walking speed associated with full robotic assistance in the chronic phase after injury produced changes in walking speed below the level of minimal detectable change (MDC; amount of change that is greater than the error of the measurement), 51 which has been identified as *0.05 to 0.1 m/sec. 122,123 We speculate that volitional effort engages the important neural circuits required for walking, which in turn induces neural plastic change.…”
Section: Key Ingredients Of Trainingmentioning
confidence: 99%
“…The clinical manifestations are associated with high morbidity and high mortality [1]. SCI not only causes severe physical and psychological damage to the patient, but also represents a considerable economic burden to society [2].…”
Section: Introductionmentioning
confidence: 99%